Comparison of colour monitor and high resolution greyscale diagnostic monitor using dedicated pacs workstation on computed radiograph of chest - Saad, Khatrulnada Md (2006)
Background: Computers and monitors are the most important tools in digital imaging. High resolution greyscale diagnostic monitor is the current gold standard for soft copy display. However, this type of monitor is very expensive and its use in clinical practice may not be cost effective. Hence, for economical reason, a hospital-wide fllmless system based on PACS equipped with workstation for viewing radiographs has not yet been accepted in HUSM. An alternative to the expensive diagnostic workstation monitor that is more cost-effective and can present comparable images must be considered. Colour monitor is considerably cheaper; however there were very few studies on the accuracy and reliability of colour monitor in the interpretation of radiographs in comparison to that of a high resolution greyscale monitor. Objectives: The aim of this study is to determine the diagnostic accuracy and reliability of colour monitor compared to high resolution greyscale diagnostic monitor on CR chest. Methodology: The institutional ethics committee approved the study; informed consent was not required. This study was a comparative cross sectional study and conducted in Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian, Kelantan. All computed chest radiographs from I June 2004 to 31 December 2005 were used as source population. A total of 136 chest images remained after the screenings. Two observers reviewed 136 CR chest images comprising of 48 normal and 88 abnormal images using colour monitor and greyscale monitor at different occasions separated between 3 - 4 weeks. The detections were scored using a scoring form. Analysis of sensitivity, specificity, accuracy and reliability were used. Results: Combination of both observers showed sensitivity of 74.8% and specificity of 94.0% for greyscale monitor and 69.2% sensitivity with 94.1% specificity for colour monitor. There was no statistical significant different for sensitivity and specificity between the two monitors at 95% confidence interval. The calculated accuracy was 91.9% for greyscale monitor and 91.5% for colour monitor. Intraobserver agreements for all the abnormalities were substantial for observer I, observer 2 and both observers combined together (k=0.748-0.767). Moderate agreement were demonstrated between the observers for greyscale (k=0.599) and colour monitor (k=0.515). Conclusion: Colour monitor was comparable to high resolution greyscale diagnostic monitor in sensitivity, specificity, accuracy and reliability for detection of chest abnormalities.